Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 115765 by aye48 last updated on 28/Sep/20

      Show that sin (α + β) = sin α cos β + cos α sin β.

Showthatsin(α+β)=sinαcosβ+cosαsinβ.

Commented by bemath last updated on 28/Sep/20

Commented by aye48 last updated on 28/Sep/20

Tk yu sir, explain step by step pl.

Tkyusir,explainstepbysteppl.

Commented by Ar Brandon last updated on 28/Sep/20

sin(α+β)=((PT)/(OP))=((RT+PR)/(OP))=((SU+PR)/(OP))                        =((SU)/(OP))+((PR)/(OP))=((SU)/(OS))×((OS)/(OP))+((PR)/(PS))×((PS)/(OP))                        =sin𝛂cos𝛃+cos𝛂sin𝛃

sin(α+β)=PTOP=RT+PROP=SU+PROP=SUOP+PROP=SUOS×OSOP+PRPS×PSOP=sinαcosβ+cosαsinβ

Answered by MJS_new last updated on 28/Sep/20

remember  sin x =((e^(ix) −e^(−ix) )/(2i))=−(i/2)(e^(ix) −(1/e^(ix) ))  cos x =((e^(ux) +e^(−ix) )/2)  ⇒  sin (α+β) =−(i/2)(e^(iα) e^(iβ) −(1/(e^(iα) e^(iβ) )))=       [let e^(iα) =p∧e^(iβ) =q]  =−(i/2)(pq−(1/(pq)))=       [now the trick:]  =−(i/4)(2pq−(2/(pq)))=  =−(i/4)(2pq−(2/(pq))+((p/q)+(q/p))−((p/q)+(q/p)))=  =−(i/4)((pq+(p/q)−(q/p)−(1/(pq)))+(pq−(p/q)+(q/p)−(1/(pq))))=  =−(i/4)((p−(1/p))(q+(1/q))+(p+(1/p))(q−(1/q)))=  =−((i(p−(1/p)))/2)×((q+(1/q))/2)−((p+(1/p))/2)×((i(q−(1/q)))/2)=  =((e^(iα) −e^(−iα) )/(2i))×((e^(iβ) +e^(−iβ) )/2)+((e^(iα) +e^(−iα) )/2)×((e^(iβ) −e^(−iβ) )/(2i))=  =sin α cos β +cos α sin β

remembersinx=eixeix2i=i2(eix1eix)cosx=eux+eix2sin(α+β)=i2(eiαeiβ1eiαeiβ)=[leteiα=peiβ=q]=i2(pq1pq)=[nowthetrick:]=i4(2pq2pq)==i4(2pq2pq+(pq+qp)(pq+qp))==i4((pq+pqqp1pq)+(pqpq+qp1pq))==i4((p1p)(q+1q)+(p+1p)(q1q))==i(p1p)2×q+1q2p+1p2×i(q1q)2==eiαeiα2i×eiβ+eiβ2+eiα+eiα2×eiβeiβ2i==sinαcosβ+cosαsinβ

Commented by Dwaipayan Shikari last updated on 28/Sep/20

Great thinking sir!

Greatthinkingsir!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com